Dysbiosis in Children With Neurological Impairment and Long-Term Enteral Nutrition - Panelli, Simona; Calcaterra, Valeria; Verduci, Elvira; Comandatore, Francesco; Pelizzo, Gloria; Borghi, Elisa; Bandi, Claudio; Zuccotti, Gianvincenzo (Frontiers in Nutrition, 2022)
Severe neurological impairment (NI) is often accompanied by the need of an artificial nutritional support, normally provided enterally (EN, enteral nutrition) to ensure growth, counteract morbidity and mortality, and improve quality of life. On the other hand, long-term EN (LTEN) may contribute to the establishment, or exacerbation, of gastrointestinal disorders that may lead to malnutrition, in turn associated with alterations in gut microbiota (GM) composition and functional capacities. In this study, we investigated, for the first time to the best of our knowledge, the consequences of LTEN in a pediatric population in this pathological context. Using amplicon sequencing, we compared the fecal microbiota of a pediatric population suffering from severe NI and under LTEN, to that of sex- and age-matched controls. The two groups presented evident differences in GM composition and a consistent differential clustering. In general, the taxonomic picture in NI children under LTEN seemed to mirror a profound dysbiotic condition, in which anti-inflammatory taxa appear severely depleted (among others, the Clostridiales families of Lachnospiraceae and Ruminococcaceae, and, within the latter, Faecalibacterium spp. and Gemmiger spp.), while known pathobionts (Gammaproteobacteria and Klebsiella) or emerging pathogens (e.g., Synergistales and Cloacibacillus, Fusobacterium) were significantly enriched. Our data suggest that LTEN can profoundly influence the GM taxonomic composition in NI children. Even if other factors are probably at work, as the bidirectional interaction between gastrointestinal impairment/immaturity and the central nervous, the assumption of drugs and physical inactivity, these data define possible routes and targets to try to alleviate this dysbiosis, with a view to better management of these patients and an improvement in their quality of life.